Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3390/molecules19067528
|View full text |Cite
|
Sign up to set email alerts
|

Structural Crystalline Characterization of Sakuranetin — An Antimicrobial Flavanone from Twigs of Baccharis retusa (Asteraceae)

Abstract: Bioactivity-guided fractionation of an antimicrobial active extract from twigs of Baccharis retusa C. DC. (Asteraceae) yielded the flavanone 5,4'-dihydroxy-7-methoxy-flavanone (sakuranetin) as responsible for the detected activity. The structure of the bioactive compound was established on the basis of spectroscopic data analysis, including NMR and MS. Additionally, the structure of a new crystal form of sakuranetin was confirmed by X-ray diffratometry. The minimum inhibitory concentrations (MIC) of isolated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…One-and two-dimensional nuclear magnetic resonance (NMR) spectra were recorded for the isolated compounds using deuterated dimethyl sulfoxide (DMSO-d 6 ). 1 H-and 13 C-NMR chemical shifts (see Supplementary Material) were in accordance with those reported for pinocembrin 1 [28][29][30], sakuranetin 2 [31][32][33][34], cirsimaritin 3 [26,[35][36][37], and naringenin 4 [27,28,[38][39][40][41]. An unambiguous assignment of the 13 C-NMR spectrum of these compounds was deduced from 1 H-1 H COSY, NOESY, HSQC, and HMBC spectra (see Supplementary Material).…”
Section: Column Chromatography Recrystallization Meohsupporting
confidence: 85%
“…One-and two-dimensional nuclear magnetic resonance (NMR) spectra were recorded for the isolated compounds using deuterated dimethyl sulfoxide (DMSO-d 6 ). 1 H-and 13 C-NMR chemical shifts (see Supplementary Material) were in accordance with those reported for pinocembrin 1 [28][29][30], sakuranetin 2 [31][32][33][34], cirsimaritin 3 [26,[35][36][37], and naringenin 4 [27,28,[38][39][40][41]. An unambiguous assignment of the 13 C-NMR spectrum of these compounds was deduced from 1 H-1 H COSY, NOESY, HSQC, and HMBC spectra (see Supplementary Material).…”
Section: Column Chromatography Recrystallization Meohsupporting
confidence: 85%
“…as the aglycone of sakuranin [17]. According to the literature, sakuranetin was shown to be the main flavonoid found in the species Baccharis retusa (family Asteraceae), a plant in southern Brazil [18] from which it was isolated and characterized.…”
Section: Sources Of Sakuranetinmentioning
confidence: 99%
“…Grecco et al showed that sakuranetin, which was extracted from twigs of Baccharis retusa, could be employed as a tool for designing novel and more efficient antifungal agents [18]. The minimum inhibitory concentration values (MIC) of the isolated compound were determined for pathogenic yeast belonging to the genus Candida (six species), Cryptococcus (two species/four serotypes) and S. cerevisiae BY 4742 (S288c background).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…As part of our continuous research aiming at the discovery of new antimicrobial agents from Brazilian plant species [16,17,18,19,20], in this work we determined the chemical composition of essential oils extracted from three different selected plant species: E. erythropappus (leaves and branches), P. barbatus (leaves), and P. amboinicus (leaves). Additionally, their antimicrobial potential against yeasts and bacteria (including some strains that displayed resistance to antibiotics [21,22] was assessed in broth microdilution assays and the minimum inhibitory concentration (MIC) was thus determined.…”
Section: Introductionmentioning
confidence: 99%